Analisis Biaya, Volume, Laba untuk Optimalisasi Operasional dan Peningkatan Laba di PT. Unilever Indonesia Tbk - Monica Anggriani Sinaga; Lilianti Tampubolon; Irmawati Simangunsong; Rita Peranita Manalu; Veny Shintiya Saragih; Yeni Enjelia Saragih; Hamonangan Siallagan (CV. Ulil Albab Corp, 2024)
This study analyzes the relationship between cost, volume, and profit (CVP) and operational optimization at PT. Unilever Indonesia Tbk. Facing increased raw material and operational costs, as well as fluctuating market demand, the company employs CVP analysis and Break-Even Point (BEP) to enhance efficiency and profitability. Data from the company's annual reports for the period 2021-2023 indicate an 8% increase in raw material costs and a 5% increase in operational costs in 2023. This research utilizes descriptive and analytical methods with secondary data from the company's financial reports, the Indonesian Central Statistics Agency (BPS), and the Indonesian Employers Association (APINDO). The results show that the company needs to produce a minimum of 500,000 units to reach the break-even point and manage costs more effectively. Operational optimization can be achieved through proper capacity planning and efficient sales strategies, adjusted for cost fluctuations and market demand. This study provides strategic recommendations for PT. Unilever Indonesia Tbk to improve profits through effective cost management and the application of CVP and BEP analysis.